E-063 The pc400 system safely coils large cerebral aneurysms with high packing densities and low retreatment rates. (23rd July 2017) - Almandoz, Delgado J; Kayan, Y; Fease, J; Scholz, J; Milner, A; Wallace, A; Mulder, M
Abstract : Purpose: The Penumbra Coil 400 System (PC400) was designed with increased coil diameter to enhance filling efficiency in large intracranial aneurysms. This study's goal is to evaluate the safety and efficacy of the PC400 coils to treat large intracranial aneurysms. Methods: We conducted a retrospective review of all consecutive patients with intracranial aneurysms treated with PC400 coils at a single center. Baseline patient and aneurysm characteristics, procedural variables and treatment-related complications were recorded. Aneurysm occlusion at the time of last angiographic follow-up was determined using the Roy-Raymond scale. Aneurysm retreatment was recorded. Results: 57 consecutive patients with 60 intracranial aneurysms were included, 44 women (77%). Mean age was 60.7 years (median 60 years, 28–89 years). 12 aneurysms were ruptured (20%). Mean maximum aneurysm size was 12mm (median 10.5mm, 5.2-22mm), mean neck size was 5mm (median 4.1mm, 1.9-15mm), mean dome to neck ratio was 2 (median 1.9, 0.8-4.2). Aneurysm locations were: 27 internal carotid artery, 10 middle cerebral artery, 8 posterior communicating artery, 6 basilar tip, 5 anterior communicating artery, and 1 each posterior inferior cerebellar, superior cerebellar, posterior cerebral and anterior cerebral arteries. Aneurysm embolization techniques were: 30 balloon-assisted coiling (50%), 18 simple coiling (30%), 8 Pipeline/coiling (13%), 3 stent-assisted coiling (5%), and 1 parent artery sacrifice (2%). 49 aneurysms were treated with PC400 coils only (82%). Mean number of PC400 coils deployed was 5.1 (median 4, 1-23), mean packing density was 34% (median 33.5%, 7-68%). Mean procedure time was 64 minutes (median 53 minutes, 23–186 minutes). There were 6 peri-procedural complications: 2 intra-operative aneurysm ruptures (3.3%), 1 coil herniation requiring stenting (1.7%), and 3 post-operative infarctions with permanent deficits (5%). Angiographic follow-up was available in 54 aneurysms (90%), mean time to last follow-up 12.2 months (median 6.5 months, 3.3-33.4 months). At last follow-up, 25 aneurysms were completely occluded (46%, Raymond 1), 20 showed residual neck (37%, Raymond 2), and 9 demonstrated residual aneurysm (17%, Raymond 3). Nine aneurysms were retreated (17%), 6 with flow-diversion and 3 with stent assisted-coiling. Compared to a prior study examining 84 large aneurysms treated with conventional coils, treatment with PC400 coils resulted in higher packing densities, faster procedure times, lower procedural complications and lower retreatment rates (Tables 1 and 2). Conclusion: The PC400 system is safe and effective for the treatment of large wide-neck intracranial aneurysms, achieving high packing densities, fast procedural times, favorable safety profile and low re-treatment rates compared to conventional coiling. Disclosures: J. Delgado Almandoz: 2; C; Penumbra, Inc. Y. Kayan: 2; C; Penumbra, Inc. J. Fease: None. J. Scholz: None. A. Milner: None. A. Wallace: None. M. Mulder: None.